Persepsi kaunselor terhadap pendedahan kendiri kepada klien dalam sesi kaunseling - Fairuz, Ibrahim (Universiti Malaysia Sarawak, UNIMAS, 2003)
Basically. this research aims to search the three things that are related to self-disclosure. which is more concern to the counselor's perception in self-disclosure towards client in counseling session. It is also to discuss whether counselor should or not to disclose themselves to the clients. Nevenheless it is also to determine the suitable level ofdisclosing and to know ifthat particular disclose can contribute to client's insight. Respondents are qualified counselors with experienced. The finding showed that counselor's selfdisclosure gives benefit to clients when it is appropriate in terms ofcounseling session. However. it is also showed that inappropriate self-disclosure can effect clients. unless the disclosure present the victory and success ofthe counselor. An impressive disclosure could contribute to client's insight. The level which is suitable for counselor to disclose is at the second stage. after the rapport has been established between the counselor and the client. The researcher thus. suggest to the counselor to preserve their credibility in other to disclose themselves towards clients. Also. future studies should be expanded to more factors rather than the one discussed in this research. Besides. it is better to diverse the method in order to gain a good feedback especially in this research.